In Vitro and In Vivo Characterization of Tebipenem, an Orally Active Carbapenem, against Biothreat Pathogens - Clayton, Nicholas P. (Antimicrob Agents Chemother, 2021)
Bacillus anthracis and Yersinia pestis, the causative pathogens for anthrax and plague, respectively, along with Burkholderia mallei and Burkholderia pseudomallei are potential bioterrorism threats. Tebipenem pivoxil hydrobromide (TBP HBr) (formerly SPR994) is an orally available prodrug of tebipenem, a carbapenem with activity versus multidrug-resistant (MDR) Gram-negative pathogens, including quinolone-resistant and extended-spectrum-β-lactamase-producing Enterobacterales. We evaluated the in vitro activity and in vivo efficacy of tebipenem against biothreat pathogens. Tebipenem was active in vitro against 30-strain diversity sets of B. anthracis, Y. pestis, B. mallei, and B. pseudomallei with MIC values of 0.001 to 0.008 μg/ml for B. anthracis, ≤0.0005 to 0.03 μg/ml for Y. pestis, 0.25 to 1 μg/ml for B. mallei, and 1 to 4 μg/ml for B. pseudomallei. In a B. anthracis murine model, all control animals died within 52 h postchallenge. The survival rates in the groups treated with tebipenem were 75% and 73% when dosed at 12 h and 24 h postchallenge, respectively. The survival rates in the positive-control groups treated with ciprofloxacin were 75% when dosed at 12 h and 25% when dosed at 24 h postchallenge. Survival rates were significantly (P = 0.0009) higher in tebipenem groups treated at 12 h and 24 h postchallenge and in the ciprofloxacin group at 12 h postchallenge than in the vehicle control group. For Y. pestis, survival rates for all animals in the tebipenem and ciprofloxacin groups were significantly (P < 0.0001) higher than for the vehicle control group. These results support the further development of tebipenem for treating biothreat pathogens.